María Laura Romano, Monstruos de la razón: Periódicos no ilustrados en la región platina: 1820-1830, Villa María, Eduvim, 2023, 446 pp. - Pose, Lucía (Badebec, 2025)
Reseña de María Laura Romano, Monstruos de la razón: Periódicos no ilustrados en la región platina: 1820-1830, Villa María, Eduvim, 2023, 446 pp.